Koordinatori i vezni adverbijali kao obeležja veze među rečenicama: prevođenje sa engleskog na srpski (Philologia, 2021)
English coordinators and linking adverbials used to connect sentences can be translated into Serbian in different ways. While their translation equivalents are typically their Serbian counterparts, there are cases where coordinators are translated by linking adverbials/particles, linking adverbials are translated by coordinators, and either coordinators or linking adverbials are translated by a combination of coordinator and linking adverbial/particle. Moreover, sometimes no translation equivalent is used. In this paper, these different cases are illustrated and described.
Keywords: koordinatori; vezni adverbijali; tekstualni konetkori; formalni korespondenti; prevodni ekvivalenti; prevođenje